Control Based on PID Framework - The Mutual Promotion of Control and Identification for Complex Systems 2021
DOI: 10.5772/intechopen.94907
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Control Approach Based on the Combination of PID Control with LQR Optimal Control

Abstract: Proportional Integral Derivative (PID) is the most popular controller that is commonly used in wide industrial applications due to its simplicity to realize and performance characteristics. This technique can be successfully applied to control the behavior of single-input single-output (SISO) systems. Extending the using of PID controller for complex dynamical systems has attracted the attention of control engineers. In the last decade, hybrid control strategies are developed by researchers using conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The careful selection of a suitable control algorithm plays a pivotal role in the effective implementation of a smart structure. This is because the control algorithm employed to regulate the control force has a substantial influence on the performance of control systems [25,26], Linear Quadratic Gaussian (LQG) [27], Instantaneous Optimal Control [2], Independent Modal Space Control [28], Bounded State Control [13], Generalized Feed-Back Control [29], Sliding Mode Control (SMC) [30], Wavelet-based control algorithm [31], H ∞ and H 2 [32], Open Loop Control [33], Clipping control [34], Direct Lyapunov control [35], Bang-bang control [36], Maximum Energy Dissipation [37], Fuzzy logic control [38,39], Neural network [40,41], and Instantaneous Optimal control [42] are the example of the well-known control strategies. According to previous studies, the classical proportional-integral-derivative (PID) controller has demonstrated efficacy [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…The careful selection of a suitable control algorithm plays a pivotal role in the effective implementation of a smart structure. This is because the control algorithm employed to regulate the control force has a substantial influence on the performance of control systems [25,26], Linear Quadratic Gaussian (LQG) [27], Instantaneous Optimal Control [2], Independent Modal Space Control [28], Bounded State Control [13], Generalized Feed-Back Control [29], Sliding Mode Control (SMC) [30], Wavelet-based control algorithm [31], H ∞ and H 2 [32], Open Loop Control [33], Clipping control [34], Direct Lyapunov control [35], Bang-bang control [36], Maximum Energy Dissipation [37], Fuzzy logic control [38,39], Neural network [40,41], and Instantaneous Optimal control [42] are the example of the well-known control strategies. According to previous studies, the classical proportional-integral-derivative (PID) controller has demonstrated efficacy [43,44].…”
Section: Introductionmentioning
confidence: 99%